Parental Communication, Engagement, and Support During the Adolescent Voluntary Medical Male Circumcision Experience. (3rd April 2018) - Dam, Kim H; Kaufman, Michelle R; Patel, Eshan U; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; Ncube, Getrude; et al.
Abstract: Background: Voluntary medical male circumcision (VMMC) is one of few opportunities in sub-Saharan Africa to engage male adolescents in the healthcare system. Limited data are available on the level of parental communication, engagement, and support adolescents receive during the VMMC experience. Methods: We conducted 24 focus group discussions with parents/guardians of adolescents (N = 192) who agreed to be circumcised or were recently circumcised in South Africa, Tanzania, and Zimbabwe. In addition, male adolescents (N = 1293) in South Africa (n = 299), Tanzania (n = 498), and Zimbabwe (n = 496) were interviewed about their VMMC experience within 7–10 days postprocedure. We estimated adjusted prevalence ratios (aPRs) using multivariable Poisson regression with generalized estimating equations and robust standard errors. Results: Parents/guardians noted challenges and gaps in communicating with their sons about VMMC, especially when they did not accompany them to the clinic. Adolescents aged 10–14 years were significantly more likely than 15- to 19-year-olds to report that their parent accompanied them to a preprocedure counseling session (56.5% vs 12.5%; P < .001). Among adolescents, younger age (aPR, 0.86; 95% confidence interval [CI], .76–.99) and rural setting (aPR, 0.34; 95% CI, .13–.89) were less likely to be associated with parental–adolescent communication barriers, while lower socioeconomic status (aPR, 1.37; 95% CI, 1.00–1.87), being agnostic (or of a nondominant religion; aPR, 2.87; 95% CI, 2.21–3.72), and living in South Africa (aPR, 2.63; 95% CI, 1.29–4.73) were associated with greater perceived barriers to parental–adolescent communication about VMMC. Parents/guardians found it more difficult to be involved in wound care for older adolescents than for adolescents <15 years of age. Conclusions: Parents play a vital role in the VMMC experience, especially for younger male adolescents. Strategies are needed to inform parents completely throughout the VMMC adolescent experience, whether or not they accompany their sons to clinics.